Table of Content - -, (Journal of natural sciences, life and applied sciences, 2023)
Table of Content:1. Producing a sweetened drink for diet using invertase enzyme extracted from some Iraqi datesDr. Zahraa S. Al-Garawi, Mr. Ahmed R. Ahmed, Mr. Ahmed M. Hussein, Mrs. Naba` S. Nasir2. The role of modern construction methods in environmental sustainability at the project siteMrs. Ibtisam Marshod Alharbi3. Assessment the horizontal micro-tunnelling discharge for torrents in Buraydah city, Al-Qassim regionMr. Fihan Mamdouh Saud Al-Rashidi4. Measurements of trees in the city of Abha using lidar technology by smart phonesMrs. Eman Saeed Al-Shahrani, Co-Prof. Sulafa Haj Al-Safi5. Evaluation of Industrial Waste in the Paints Industry Sector:  Khartoum North Industrial Area,Dr. Mona Ali Mohamed Ahmed
Keywords: Journal of Natural Sciences, Life and Applied Sciences